THE FRAUD OF BANKING REVIEW IN LEGAL PERSPECTIVE - Novi Angga Safitri; Jefry Tarantang; Rahmad Kurniawan; Tri Anshari Muharrami (International Journal of Law Reconstruction, 2022)
The fraud is one of the things that can be done by someone, from the mild to the most severe level of cheating. Fraud is one of the acts of fraud and fraud committed by certain groups in obtaining personal gain and of course having a fairly large level of loss. This research aims to explain the ideas and theories and characteristics of perpetrators of fraud, how to resolve the law that must be enforced in order to face judicial problems and risks for perpetrators and ways and strategies to overcome fraud that occurs within the scope of banking. This study used a method in literature and library research, namely analysis in the form of discussions related to legal ideas, theories and the occurrence of fraud in the banking law perspective so that conclusions can then be drawn in understanding the extent to which actions based on fraud perpetrators can harm themselves or loss to another person/party. Losses caused by fraud are very large losses and can be widespread in the scope of banking. In addition, the bank really avoids all forms of loss, one of which is reputation risk which greatly affects the quality of the bank because it can give a bad image and influence to the wider community due to cases of fraud or fraud. The fraud prevention strategy is in the form of a systematic form that exists in controlling fraud, in this case management is required to mobilize productivity and quality resources so that the strategy in controlling prevention can continue and provide useful effects in reducing fraud cases.